Analysis of the screening and predicting characteristics of the house-tree-person drawing test for mental disorders: A systematic review and meta-analysis - Guo, Huibing; Feng, Bin; Ma, Yingqiao; Zhang, Xueyi; Fan, Huiyong; Dong, Zaiquan; Chen, Taolin; Gong, Qiyong (Frontiers in Psychiatry, 2023)
House-Tree-Person Drawing Test (HTP) has received growing attention from researchers as a common projective test. However, the selection and interpretation of drawing indicators still lack uniformity. This study conducted a systematic review and meta-analysis of the application of HTP to integrate drawing indicators that can screening or classifying mental disorders. A search of the following electronic databases was performed in May 2022: PubMed, Web of Science, Embase, EBSCO, CNKI, VIP, and Wanfang. Screening and checking of the literature were performed independently by two researchers, published empirical studies of HTP test in mental disorders and those providing specific data on the occurrence frequency of drawing characteristics were included. A total of 30 studies were included in the meta-analysis, including 665 independent effect sizes and 6,295 participants. The strength of the association between drawing characteristics of the HTP test and the prevalence of mental disorders was measured by the ratio (OR) and 95%CI. Publication bias was assessed using a funnel plot, Rosenthal's fail-safe number (Nfs), and the trim and fill method. The results revealed 50 drawing characteristics that appeared at least three times in previous studies, of which 39 were able to significantly predict mental disorders. HTP can be divided into four dimensions: House, Tree, Person, and the Whole containing the above three. Results showed that the greatest predictor of mental disorders was the Whole (OR=4.20, p<0.001), followed by House (OR=3.95, p<0.001), Tree (OR=2.70, p<0.001), and Person (OR=2.16, p<0.001). The valid predictors can be categorized as four types: items absence, bizarre or twisted, excessive details, and small or simplified. Subgroup analysis showed that affective-specific indicators included no motion, leaning house and decorated roof, thought-specific indicators included excessive separation among items, no window, loss of facial features and inappropriate body proportions, and common indicators of mental disorders included no additional decoration, simplified drawing, very small house, two-dimensional house and very small tree. Therefore, this study can promote the standardization of HTP and provide a theoretical reference for screening and clinical diagnosis of mental disorders.